VLSI testing digital and mixed analogue/digital techniques - Hurst, Stanley L. (Institution of Engineering and Technology, 1998)
The importance of testing integrated circuits (ICs) has escalated with the increasing complexity of circuits fabricated on a single IC chip. No longer is it possible to design a new IC and then think about testing: such considerations must be part of the initial design activity, and testing strategies should be part of every circuit and system designer's education. This book is a comprehensive introduction and reference for all aspects of IC testing. It includes all of the basic concepts and theories necessary for advanced students, from practical test strategies and industrial practice, to the economic and managerial aspects of testing. In addition to detailed coverage of digital network testing, VLSI testing also considers in depth the growing area of testing analogue and mixed analogue/digital ICs, used particularly in signal processing.